Feasibility, coverage and cost of oral cholera vaccination conducted by icddr,b using the existing national immunization service delivery mechanism in rural setting Keraniganj, Bangladesh - Ashraful Islam Khan; Iqbal Ansary Khan; Shah Alam Siddique; Anisur Rahman; Md. Taufiqul Islam; Md Amirul Islam Bhuiya; Nirod Chandra Saha; Prasanta Kumar Biswas; Amit Saha; Fahima Chowdhury; Firdausi Qadri (Taylor & Francis Group, 2019)
Background: Cholera is a considerable health burden in developing country settings including Bangladesh. The oral cholera vaccine (OCV) is a preventative tool to control the disease. The objective of this study was to describe whether the International Centre for Diarrheal Disease Research, Bangladesh (icddr,b), could provide the OCV to rural communities using existing government infrastructure. Methods: The study was conducted in rural sub-district Keraniganj, 20 km from the capital city Dhaka. All listed participants one year and above in age (excluding pregnant women) were offered two doses of OCV at a 14 day interval. Existing government facilities were used to deliver and also maintain the cold chain required for the vaccine. All events related to vaccination were recorded at the 17 vaccination sites to evaluate the coverage and feasibility of OCV program. Results: A total of 29,029 individuals received the 1st dose (90% of target) and 26,611 individuals received the 2nd dose (83% of target and 92% of 1st dose individuals) of OCV. The highest vaccination coverage was in younger children (1-9 years) and the lowest was amongst 18-29-year age group. Somewhat better coverage was seen amongst the female participants than males (92% vs. 88% for the 1st dose and 93% vs. 90% for the 2nd dose). The cost of vaccine cost was calculated as US$1.00 per dose plus freight, insurance, and transportation and the total vaccine delivery cost was US$70,957. Conclusion: This was a project undertaken using existing public health program resources to collect empirical evidence on the use of a mass OCV campaign in the rural setting. Mass vaccination with the OCV is feasible in the rural setting using existing governmental vaccine delivery systems in Bangladesh.